Advanced Glycation End Products Play Adverse Proinflammatory Activities in Osteoporosis - Roberta Sanguineti; Alessandra Puddu; François Mach; Fabrizio Montecucco; Giorgio Luciano Viviani (Mediators of Inflammation)
Osteoporosis is a major public health burden that is expected to further increase as the global population ages. In the last twenty years, advanced glycation end products (AGEs) have been shown to be critical mediators both in the pathogenesis and development of osteoporosis and other chronic degenerative diseases related to aging. The accumulation of AGEs within the bone induces the formation of covalent cross-links with collagen and other bone proteins which affects the mechanical properties of tissue and disturbs bone remodelling and deterioration, underlying osteoporosis. On the other hand, the gradual deterioration of the immune system during aging (defined as immunosenescence) is also characterized by the generation of a high level of oxidants and AGEs. The synthesis and accumulation of AGEs (both localized within the bone or in the systemic circulation) might trigger a vicious circle (in which inflammation and aging merged in the word “Inflammaging”) which can establish and sustain the development of osteoporosis. This narrative review will update the molecular mechanisms/pathways by which AGEs induce the functional and structural bone impairment typical of osteoporosis.